Improving Policy for the Prevention of Falls Among Community-Dwelling Older People-A Scoping Review and Quality Assessment of International National and State Level Public Policies - Aleksandra H. Natora; Aleksandra H. Natora; Jennifer Oxley; Linda Barclay; Kelvin Taylor; Bruce Bolam; Terry P. Haines; Terry P. Haines (Frontiers Media S.A., 2022)
Objectives: Effective public policy to prevent falls among independent community-dwelling older adults is needed to address this global public health issue. This paper aimed to identify gaps and opportunities for improvement of future policies to increase their likelihood of success.Methods: A systematic scoping review was conducted to identify policies published between 2005-2020. Policy quality was assessed using a novel framework and content criteria adapted from the World Health Organization's guideline for Developing policies to prevent injuries and violence and the New Zealand Government's Policy Quality Framework.Results: A total of 107 articles were identified from 14 countries. Content evaluation of 25 policies revealed that only 54% of policies met the WHO criteria, and only 59% of policies met the NZ criteria. Areas for improvement included quantified objectives, prioritised interventions, budget, ministerial approval, and monitoring and evaluation.Conclusion: The findings suggest deficiencies in a substantial number of policies may contribute to a disconnect between policy intent and implementation. A clear and evidence-based model falls prevention policy is warranted to enhance future government efforts to reduce the global burden of falls.